Evaluación de accesibilidad a la página web de la carrera de Computación de la Universidad Nacional de Loja - Villavicencio Aldaz, José Xavier (2025)
The feature of web accessibility is crucial for many people, especially those with disabilities, and that is why the WCAG guidelines are essential for evaluating this characteristic on websites. The objectives of this ICT project are to assess the level of accessibility of the Computing career website and to solve the main accessibility issues of the Computing career website by applying WCAG compliance criteria. The methodology used in this project was based on two phases corresponding to each objective. The first phase consisted of a systematic literature review applying Barbara Kitchenham's methodology, which synthesizes and analyzes articles related to web accessibility published in databases such as Scopus, IEEE Xplore, and ACM Digital Library. The results obtained include accessibility issues, techniques, and tools, which were used to evaluate the career website. Based on the results from the first phase, where evaluation tables were created and the issues to be solved were identified, the second phase was developed, which consisted of implementing the necessary changes to the career website, using sufficient techniques to meet the compliance criteria established for solving auditory accessibility issues. Finally, the changes were verified using the WAVE and Access Monitor automatic evaluation tools, where the proper resolution of the accessibility issues was confirmed. As a result, the research question regarding the level of accessibility of the Computing career website was answered. Keywords: web accessibility, accessibility standards, automatic tools, manual evaluation, accessibility issues.